INVESTMENT FINANCING THROUGH THE "PROJECT FINANCE" - Molina Arenaza, Hércules (2004)
This article analizes and compares the various aspects related to the "Project Finance" technique using projects financing in the Capital Market, both in developed countries and in developing countries. Likewise, the application's technique is illustrated by Antamina mining enterprise.